(untitled) (Publicacions de la Universitat de València, 2021)
The agri-food sector encompasses an extremely wide range of activities regarding the entire value chain of a product and generates a huge volume of work for translators. Nevertheless, the sheer proportion has yet to be truly reflected in academic studies and research. This work intends to shed light on the vague, and barely addressed until now, delimitation of the area of activity of the multifaceted and versatile agri-food translator. Through a text typologisation of genres and subgenres, within the margins of hybridity, specialisation and register, this work approaches the characteristics of scientific-technical, medical-health, legal-administrative, humanistic-literary, tourist, advertising and gastronomic and culinary agri-food texts, and assesses the skills required from their translator. El sector agroalimentari abasta un amplíssim ventall d’activitats relatives a tota la cadena de valor d’un producte que generen un enorme volum de traduccions; tanmateix, les investigacions i els estudis acadèmics a penes s’han ocupat d’aquesta especialitat fins ara. Aquest treball pretén llançar llum sobre la poca delimitació de l’àmbit d’activitat del polifacètic i versàtil traductor agroalimentari i, a través d’una tipologia textual de gèneres i subgèneres, dins dels marges de la hibridesa, l’especialització i el registre, fer una aproximació a les característiques dels textos cientificotècnics, medicosanitaris, juridicoadministratius, humanisticoliteraris, turístics, publicitaris i gastronòmics i culinaris agroalimentaris, i avaluar les competències que n’exigeix la traducció.